A comparative study on health risk behaviours among adolescent high school students of urban and rural areas of Raichur district, Karnataka - Vignesh B.; Sujatha N.; Arshiya Taranum; Boramma G. (International Journal Of Community Medicine And Public Health, 2026)
Background: Objectives of the study were to compare the prevalence and pattern of health risk behaviours among adolescent high school students in urban and rural areas of Raichur district, and to assess associated socio-demographic factors influencing these behaviours. Methods: A pre-tested WHO GSHS-based questionnaire was used in a school-based cross-sectional comparative study with 560 kids from August to October of 2025. Results: The sociodemographic features of the two groups were comparable. Students from urban areas had greater levels of screen usage, poor eating habits, and physical inactivity. Students in rural areas were more physically active but also had higher absence and sleep deprivation rates. Overall, drug use was minimal, but in rural areas, it was marginally higher. There was a lot of academic stress in both groups. Conclusions: Adolescent risk behaviors varied significantly across urban and rural areas, underscoring the need for focused, school-based interventions.